Implementasi Media Google Classroom dalam Pembelajaran Teks Cerita Hikayat Kelas X-5 di SMA N 11 Semarang - Nurus Sa’adah; Hana SilmaHadana; Titis Ardyasti; Asep Purwo Yudi Utomo; Eva Wulandari; Rossi Galih Kesuma; Zabidi Agus Winanto (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2024)
Cross-age stories or also known as hikayat story texts have their own uniqueness when compared to other types of texts. The uniqueness of the hikayat story text is in the presentation of the language in the story that uses archaic language, the contents of the story, and the plot used in the story. These uniqueness certainly requires an effective strategy in the learning process. After the Covid-19 pandemic has changed many aspects of human life, one of the aspects that has an impact is the field of education. In the field of education that is very influential is an educator or teacher. A teacher is required to always update and actualize the times and technology in relation to the learning process. Teachers must find alternative solutions to various problems for the smoothness and achievement of learning. One alternative solution to this problem is the implementation of Google Classroom media with a hybrid learning system. The hybrid teaching and learning process can use the help of electronic technology, one of which is Google Classroom. The method used is descriptive qualitative. The purpose of this article is to describe the implementation of Google Classroom in teaching story texts for class X-5 at SMA N 11 Semarang. The results obtained from this article are that the implementation of Google classroom in learning story texts for class X-5 at SMA N 11 Semarang runs well and smoothly and can improve student learning outcomes. Keywords: technology, media google classroom, hikayat story text